Squamous Cell Carcinoma With Perineural and Intraneural Invasion Associated With Hyalinized Tumor Nodules: A Diagnostic Pitfall and Review of the Literature. (June 2015) - Murphy, Claire; Zhao, Ge; Berg, Daniel; Olson, Jonathan; Argenyi, Zsolt
Abstract : Abstract: Cutaneous squamous cell carcinoma with perineural invasion (PNI) is an important inconspicuous finding. We report a case of a common tumor with an uncommon finding. A 57-year-old white man presented with paresthesias and a new lesion at the site of a previously resected squamous cell carcinoma. At the time of case review, present deep in the dermis, were large hyalinized tumor nodules. These nodules could have easily have been dismissed as sclerotic tumor nodules or fibrotic in-transit metastases. With the clinical history in mind, these nodules were further investigated by immunohistochemistry and reviewed in conjunction with the Mohs frozen section slides. These nodules were subsequently diagnosed as significant peri- and intraneural invasion. This extremely unusual presentation of PNI is a potential diagnostic pitfall that is potentially under-recognized by dermatopathologists but crucial for determining patient management.